Efficacy and safety of traditional Chinese medicine external washing in the treatment of postoperative wound of diabetes complicated with anal fistula: Study protocol of a randomized, double-blind, placebo-controlled, multi-center clinical trial - Kang, Jian; Liu, Ya; Peng, Sihan; Tang, Xiao; Liu, Lu; Xie, Ziyan; He, Yuchi; Zhang, Xiyu (Frontiers in Pharmacology, 2022)
Introduction Anal fistula is one of the commonest ailments seen by anorectal surgeons as surgery is currently the preferred treatment for it. Diabetes mellitus is a risk factor that can lead to slow wound healing after anal fistula surgery. Because of the large postoperative wound surface of anal fistula, patients with diabetes can have an increased probability of wound infection, which makes it hard to heal. There is extensive clinical experience for wound healing in Traditional Chinese medicine (TCM). Jiedu Shengji decoction (JSD) is a widely used external washing decoction in clinical practice. However, the current evidence on it is still insufficient. Therefore, we report this carefully designed clinical trial to assess the efficacy and safety of JSD in the treatment of postoperative wounds in diabetic patients with anal fistula. Methods and analysis This study was designed to be a randomized, double-blind, placebo-controlled, multi-center clinical trial. There will be 60 eligible participants who will be randomized at 1:1 to the intervention and placebo groups. Both groups will receive the same standard treatment. The intervention group will be given external washing decoction of TCM (JSD). While the placebo group will be given placebo made of excipients and flavoring agents. Main outcome measures include wound healing, distribution of wound pathogens, levels of inflammatory mediators, and blood glucose. Secondary outcome measures included lipids, the quality of life evaluation scale (Short-Form Health Survey 36). Assessments will be performed before the start of the study, at 1st, 2nd, 3rd, 4th week after the intervention, and at 8th, 12th, 16th follow-up week. Discussion The clinical study we propose will be the first randomized, double-blind, placebo-controlled, multicenter clinical trial study to assess the efficacy and safety of TCM external washing (JSD) in the treatment of postoperative wounds in diabetic patients with anal fistula. Ethics and dissemination The Medical Ethics Committee of Hospital of Chengdu University of Traditional Chinese Medicine has reviewed this study protocol and gave its approval and consent on 17 March 2022 (Ethical Review Number: 2022KL-018).